Oxidative degradation resistant polycarbonate polyurethane as well as preparation method and application thereof
By modifying the combination of polycarbonate diol and hydroxy-terminated polydimethylsiloxane with diisocyanate and chain extender, block polymers are formed, improving the compatibility of hard and soft segments of polycarbonate polyurethane , solves the problem of insufficient antioxidant degradation ability and mechanical properties, and achieves efficient preparation suitable for long-term implantation of biological materials.
Patent Information
- Application Number
- CN202411286004.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing polycarbonate-based polyurethanes have poor compatibility with hard and soft segments, resulting in poor antioxidant degradation ability and mechanical properties, which limits their application in biological implantable materials.
Antioxidant degraded polycarbonate polyurethane was prepared by two-step body synthesis method, and modified polycarbonate diol and hydroxyl-terminated polydimethylsiloxane were used as soft chain segments, and diisocyanate and chain extender were used as hard chain segments. Block polymers are formed, increasing hydrogen bond interactions between hard and soft segments, improving compatibility and introducing chain extenders to increase molecular chain entanglement density.
It realizes the excellent mechanical properties, antioxidant degradation properties and biocompatibility of polycarbonate polyurethane, and is suitable for long-term implantation of biological materials, reducing solvent recovery and treatment costs.
Smart Images

Figure CN119219883A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical polymer materials, and specifically relates to an antioxidant degradation polycarbonate polyurethane and a preparation method and application thereof. Background Art
[0002] Polyurethane is a polymer material containing ethyl carbamate or ethyl carbamate-carboxylic acid bonds in the main chain. It has good biocompatibility, excellent mechanical properties and molecular designability. Polyurethane has unique advantages and application background in the field of biomaterials.
[0003] The soft segment of polyurethane is composed of macromolecular diols, and the hard segment is composed of diisocyanates and chain extenders. Due to their thermodynamic incompatibility, they form a unique microphase structure. The ester bonds in polyester polyol polyurethane are easily hydrolyzed and degraded in the human body, making it difficult to use as a long-term implant material; the ether bonds of polyether polyurethane are easily oxidized and degraded, and the ether bonds of polyether polyurethane are closely related to Ca 2+ The interaction between polycarbonate and polyurethane makes it very easy to calcify. In recent years, polycarbonate-based polyurethane has attracted extensive attention from researchers. Its carbonate bond is considered to be stable in the body, not prone to hydrolysis and oxidation, and is more suitable for the preparation of long-term implant materials.
[0004] Introducing polydimethylsiloxane (PDMS) as a soft segment in polyurethane is a common method to improve the in vivo stability of polyurethane. This effect is attributed to the low surface energy of PDMS, which migrates and accumulates on the surface of the material to form a protective layer, thereby improving the stability of polyurethane in vivo. However, recent studies have also shown that the inherent low polarity of PDMS leads to undesirable compatibility between hard segments and soft segments. Therefore, the exposed soft segments are more susceptible to chemical degradation, further compromising the mechanical properties of polyurethane, thereby limiting its scope of application.
[0005] LifePolymer TM It is a silicon-containing polyether polyurethane material that adds a controlled amount of polar functional groups to the copolymer diol (polyether diol and PDMS) to enhance the attraction between molecules and improve the compatibility between soft and hard segments. Therefore, the material has excellent tensile strength, tear strength and creep resistance. However, during long-term implantation, the material is at risk of oxidative degradation and reduced tensile properties.
[0006] Therefore, studying a polyurethane material that is resistant to oxidative degradation, has stable long-term mechanical properties and good biocompatibility has important clinical value in the field of biological implant materials. Summary of the invention
[0007] In view of the above-mentioned prior art, the present invention discloses an antioxidant degradation polycarbonate polyurethane and a preparation method and application thereof, so as to solve the technical problem in the prior art that the polycarbonate-based polyurethane has poor antioxidant degradation ability and poor mechanical properties due to poor compatibility between hard segments and soft segments.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing an oxidatively degradable polycarbonate polyurethane, which comprises the following steps:
[0009] S1: Mixing the vacuum-dried polycarbonate diol, diisocyanate and a catalytic amount of a catalyst, and reacting them for 2 to 3 hours under the protection of an inert gas to obtain a modified polycarbonate diol, wherein the reaction temperature is 80 to 85° C. and the catalyst is an organic metal catalyst;
[0010] S2: vacuum drying the modified polycarbonate diol and the hydroxyl-terminated polydimethylsiloxane, mixing the dried modified polycarbonate diol, the dried hydroxyl-terminated polydimethylsiloxane, the diisocyanate and a catalytic amount of a catalyst, and reacting them for 1.5 to 2 hours under the protection of an inert gas at a reaction temperature of 70 to 80° C.;
[0011] S3: After the reaction liquid in step S2 is cooled to 45-50° C., a chain extender is added to the reaction liquid, and the mixture is stirred evenly and solidified to obtain the product.
[0012] Based on the above technical solution, the present invention can also be improved as follows.
[0013] Furthermore, the diisocyanate is at least one of isophorone diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 4,4'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate and meta-xylylene diisocyanate; the organic metal catalyst is dibutyltin dilaurate or bismuth laurate; and the inert gas is N2.
[0014] Furthermore, in step S1, the drying vacuum degree is 20-40 KPa, the drying temperature is 100-110° C., and the drying time is 2-2.5 h.
[0015] Furthermore, in step S1, the polycarbonate diol is (1,4-butanediol carbonate) diol with a molecular weight of 500 to 2000 and / or poly (1,6-hexanediol carbonate) diol with a molecular weight of 500 to 2000; the molar ratio of the polycarbonate diol to the diisocyanate is 2 to 2.2:1.
[0016] Furthermore, in step S2, the drying vacuum degree is 20-40 KPa, the drying temperature is 90-110° C., and the drying time is 1.5-2 h.
[0017] Furthermore, the hydroxyl-terminated polydimethylsiloxane in step S2 is at least one of hydroxymethyl-terminated polydimethylsiloxane with a molecular weight of 500 to 2000, hydroxyethyl-terminated polydimethylsiloxane with a molecular weight of 500 to 2000, hydroxybutyl-terminated polydimethylsiloxane with a molecular weight of 500 to 2000, and ethylene glycol propyl ether-terminated polydimethylsiloxane with a molecular weight of 500 to 2000; the mass ratio of the modified polycarbonate diol to the modified polydimethylsiloxane diol is 4:1; and the ratio of the isocyanate index NCO / OH in the reaction system of step S2 is 1.01 to 1.05.
[0018] Furthermore, the chain extender in step S3 is one or two of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane, 1,4-butanediol and 1,6-hexanediamine. When the chain extender includes two components, the molar ratio of the two chain extenders is 1:1; and the total content of diisocyanate and chain extender in the obtained antioxidant degradation polycarbonate polyurethane is 43-47wt%.
[0019] The beneficial effects of the above steps of the present invention are as follows: the diisocyanate and the chain extender are used as hard segments, the hard chain content has an appropriate microphase separation degree, and the compatibility between the hard segment and the soft segment is good.
[0020] Furthermore, in step S3, the total time for adding the chain extender and stirring is 30 to 60 seconds; the curing temperature is 100 to 120° C., and the curing time is 8 to 10 hours.
[0021] The invention also discloses the application of the above anti-oxidation degradation polycarbonate polyurethane in the preparation of medical implant materials.
[0022] The beneficial effects of the present invention are:
[0023] 1. The present invention adopts a two-step bulk synthesis method to prepare antioxidant degradation polycarbonate polyurethane, and no solvent is used in the reaction process, thereby reducing the cost of solvent recovery and treatment; the prepared antioxidant degradation polycarbonate polyurethane has excellent mechanical properties, antioxidant degradation properties and biocompatibility, and can be used to prepare long-term implantable biomaterials.
[0024] 2. The antioxidant degradation polycarbonate polyurethane in the present invention is a block polymer composed of modified polycarbonate diol and hydroxyl-terminated polydimethylsiloxane as soft segments, and diisocyanate and chain extender as hard segments. The modified polycarbonate diol changes the structure of hydrogen bonds, increases the content of hydrogen bonds between the NH group of the hard segment and the C=O group of the soft segment, enhances the interaction force between the soft segment and the hard segment, promotes phase mixing, makes the soft segment less exposed to the outside, is not easily chemically eroded, and maintains excellent antioxidant degradation performance. In addition, the formation of hydrogen bonds between the NH group of the hard segment and the C=O group of the soft segment makes the hard segment have a higher solubility in the soft segment, and the soft segment and the hard segment have good compatibility, which further makes the soft segment less susceptible to erosion by external chemical substances.
[0025] 3. The chain extender is introduced into the antioxidant polycarbonate polyurethane of the present invention, which increases the entanglement density of the molecular chains in the polymer matrix, affects the microphase separation behavior, and is conducive to the migration of hydroxyl-terminated polydimethylsiloxane fragments to the surface of the polycarbonate-based polyurethane to form an antioxidant degradation protective layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the infrared spectrum of the sample prepared in Comparative Example 1;
[0027] Figure 2 is the infrared spectrum of the sample prepared in Example 1;
[0028] Figure 3 DSC heat flow curves of samples of Example 1 and Comparative Example 1;
[0029] Figure 4 It is the full XPS spectra of the samples of Example 1 and Comparative Example 1;
[0030] Figure 5 The Si element fine spectra of the samples of Example 1 and Comparative Example 1 are shown;
[0031] Figure 6 The stress-strain relationship diagram of the samples of Example 1 and Comparative Example 1 and the samples after oxidation for 12 weeks;
[0032] Figure 7 The SEM images of the samples of Example 1 and Comparative Example 1 and after oxidation for different time periods;
[0033] Figure 8 HE staining images of the samples of Example 1 and Comparative Example 1 after being implanted subcutaneously into rats for 7 days and 15 days. DETAILED DESCRIPTION
[0034] The specific implementation modes of the present invention are described in detail below with reference to the embodiments.
[0035] Example 1
[0036] An antioxidant polycarbonate polyurethane, the preparation method of which comprises the following steps:
[0037] S1: Dry poly(1,4-butylene carbonate) diol with a molecular weight of 1000 in a vacuum drying oven at a temperature of 105°C for 2h to remove moisture, and the drying vacuum degree is 30KPa, then weigh 20g of the dried poly(1,4-butylene carbonate) diol into a 25mL three-necked flask, blow N2 into it, and add 2.5g of 4,4'-dicyclohexylmethane diisocyanate to the three-necked flask, and then add 50μL of dibutyltin dilaurate with a concentration of 1wt‰, and after the addition, raise the temperature to 80°C, and keep the reaction for 3h under the protection of N2 to obtain a modified polycarbonate diol;
[0038] S2: The modified polycarbonate diol and the polydimethylsiloxane terminated with ethylene glycol propyl ether having a molecular weight of 2000 were dried in a vacuum drying oven at a temperature of 105°C for 2 hours to remove moisture. The drying vacuum degree was 30 KPa. Then 20 g of the dried modified polycarbonate diol and 5 g of the dried polydimethylsiloxane terminated with ethylene glycol propyl ether were weighed into a 25 mL three-necked flask, N2 was introduced, 13.4 g of 4,4'-dicyclohexylmethane diisocyanate was added, and then 50 μL of dibutyltin dilaurate having a concentration of 1 wt‰ was added. After the addition was completed, the temperature was raised to 80°C and the reaction was kept warm for 2 hours under the protection of N2.
[0039] S3: When the reaction liquid in step S2 is cooled to 45°C, 1.72 g of 1,4-butanediol and 5.33 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane are quickly added to the reaction liquid, and the mixture is quickly stirred evenly. The total time of addition and stirring is controlled to be 30 seconds. The product is then poured into a polytetrafluoroethylene tray, and then placed in a 100°C oven for curing for 8 hours.
[0040] Example 2
[0041] An antioxidant polycarbonate polyurethane, the preparation method of which comprises the following steps:
[0042] S1: Dry poly(1,6-hexanediol carbonate) diol with a molecular weight of 500 in a vacuum drying oven at a temperature of 110°C for 2.5 hours to remove moisture, and the drying vacuum degree is 20KPa, then weigh 20g of the dried poly(1,6-hexanediol carbonate) diol into a 25mL three-necked flask, blow N2 into it, and add 4.6g of 4,4'-methylenebis(phenyl isocyanate) to the three-necked flask, and then add 50μL of dibutyltin dilaurate with a concentration of 1wt‰, and after the addition, raise the temperature to 85°C, and keep the reaction for 2 hours under the protection of N2 to obtain a modified polycarbonate diol;
[0043] S2: The modified polycarbonate diol and the hydroxymethyl-terminated polydimethylsiloxane with a molecular weight of 500 were dried in a vacuum drying oven at a temperature of 110°C for 1.5 hours to remove moisture. The drying vacuum degree was 20 KPa. Then 20 g of the dried modified polycarbonate diol and 5 g of the dried hydroxymethyl-terminated polydimethylsiloxane were weighed into a 25 mL three-necked flask, N2 was introduced, 14.76 g of 4,4'-methylenebis(phenyl isocyanate) was added, and then 50 μL of dibutyltin dilaurate with a concentration of 1 wt‰ was added. After the addition was completed, the temperature was raised to 70°C, and the reaction was kept warm for 2 hours under the protection of N2;
[0044] S3: When the reaction liquid in step S2 is cooled to 50°C, 1.39 g of 1,4-butanediol and 4.30 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane are quickly added to the reaction liquid, and the mixture is quickly stirred evenly. The total time of addition and stirring is controlled to be 60 s, and then the product is poured into a polytetrafluoroethylene tray, and then placed in a 120°C oven for curing for 10 hours.
[0045] Example 3
[0046] An antioxidant polycarbonate polyurethane, the preparation method of which comprises the following steps:
[0047] S1: Dry poly(1,4-butylene carbonate) diol with a molecular weight of 1000 and poly(1,6-hexane carbonate) diol with a molecular weight of 1000 in a vacuum drying oven at a temperature of 100°C for 2.5 hours to remove moisture, and the drying vacuum degree is 40KPa, then weigh 10g of the dried poly(1,4-butylene carbonate) diol and 10g of the dried poly(1,6-hexane carbonate) diol into a 25mL three-necked flask, blow N2 into it, and add 2.1g of isophorone diisocyanate to the three-necked flask, and then add 50μL of dibutyltin dilaurate with a concentration of 1wt‰, and after the addition, raise the temperature to 83°C, and keep the reaction for 2.5 hours under the protection of N2 to obtain a modified polycarbonate diol;
[0048] S2: The modified polycarbonate diol and the hydroxyethyl-terminated polydimethylsiloxane with a molecular weight of 2000 were dried in a vacuum drying oven at a temperature of 90°C for 2h to remove moisture. The drying vacuum degree was 40KPa. Then 20g of the dried modified polycarbonate diol and 5g of the dried hydroxyethyl-terminated polydimethylsiloxane were weighed into a 25mL three-necked flask, N2 was introduced, 14.3g of isophorone diisocyanate was added, and then 50μL of dibutyltin dilaurate with a concentration of 1wt‰ was added. After the addition was completed, the temperature was raised to 70°C and kept warm for reaction for 1.5h under N2 protection;
[0049] S3: When the reaction liquid in step S2 is cooled to 50°C, 6.15 g of 1,6-hexanediamine is quickly added to the reaction liquid and quickly stirred evenly. The total time of adding and stirring is controlled to be 40 seconds. Then, the product is poured into a polytetrafluoroethylene tray and placed in a 110°C oven for curing for 8 hours.
[0050] Example 4
[0051] An antioxidant polycarbonate polyurethane, the preparation method of which comprises the following steps:
[0052] S1: Dry poly(1,4-butylene carbonate) diol with a molecular weight of 1500 in a vacuum drying oven at a temperature of 105°C for 2h to remove moisture, and the drying vacuum degree is 30KPa, then weigh 20g of the dried poly(1,4-butylene carbonate) diol into a 25mL three-necked flask, blow N2 into it, and add 1.1g of hexamethylene diisocyanate to the three-necked flask, and then add 50μL of bismuth laurate with a concentration of 1wt‰, and after the addition, raise the temperature to 85°C, and keep the reaction for 2h under the protection of N2 to obtain a modified polycarbonate diol;
[0053] S2: The modified polycarbonate diol and the hydroxybutyl-terminated polydimethylsiloxane with a molecular weight of 1500 were dried in a vacuum drying oven at a temperature of 90°C for 2h to remove moisture. The drying vacuum degree was 30KPa. Then 20g of the dried modified polycarbonate diol and 5g of the dried hydroxybutyl-terminated polydimethylsiloxane were weighed into a 25mL three-necked flask, N2 was blown in, 10.66g of hexamethylene diisocyanate was added, and then 50μL of bismuth laurate with a concentration of 1wt‰ was added. After the addition was completed, the temperature was raised to 70°C and kept warm for reaction for 2h under N2 protection;
[0054] S3: When the reaction liquid in step S2 is cooled to 45°C, 2.39 g of 1,4-butanediol and 7.40 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane are quickly added to the reaction liquid, and the mixture is quickly stirred evenly. The total time of addition and stirring is controlled to be 50 s, and then the product is poured into a polytetrafluoroethylene tray, and then placed in a 110°C oven for curing for 8 hours.
[0055] Example 5
[0056] An antioxidant polycarbonate polyurethane, the preparation method of which comprises the following steps:
[0057] S1: Dry poly(1,6-hexanediol carbonate) diol with a molecular weight of 2000 in a vacuum drying oven at a temperature of 100°C for 2h to remove moisture, and the drying vacuum degree is 30KPa, then weigh 20g of the dried poly(1,6-hexanediol carbonate) diol into a 25mL three-necked flask, blow N2 into it, and add 0.8g of toluene diisocyanate to the three-necked flask, and then add 50μL of dibutyltin dilaurate with a concentration of 1wt‰, and after the addition, raise the temperature to 85°C, and keep the reaction under N2 protection for 3h to obtain a modified polycarbonate diol;
[0058] S2: The modified polycarbonate diol, the ethylene glycol propyl ether-terminated polydimethylsiloxane with a molecular weight of 2000 and the hydroxyethyl-terminated polydimethylsiloxane with a molecular weight of 2000 were dried in a vacuum drying oven at a temperature of 105°C for 2h to remove moisture. The drying vacuum degree was 30KPa. Then 20g of the dried modified polycarbonate diol, 2.5g of the dried ethylene glycol propyl ether-terminated polydimethylsiloxane and 2.5g of the dried hydroxyethyl-terminated polydimethylsiloxane were weighed in a 25mL three-necked flask, N2 was introduced, 10.2g of toluene diisocyanate was added, and then 50μL of dibutyltin dilaurate with a concentration of 1wt‰ was added. After the addition was completed, the temperature was raised to 75°C and kept warm for reaction for 2h under N2 protection;
[0059] S3: When the reaction liquid in step S2 is cooled to 48°C, 2.97 g of 1,6-hexanediamine and 7 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane are quickly added to the reaction liquid, and the mixture is quickly stirred evenly. The total time of adding and stirring is controlled to be 60 seconds. The product is then poured into a polytetrafluoroethylene tray, and then placed in a 120°C oven for curing for 10 hours.
[0060] Example 6
[0061] An antioxidant polycarbonate polyurethane, the preparation method of which comprises the following steps:
[0062] S1: Dry poly(1,4-butylene carbonate) diol with a molecular weight of 1000 in a vacuum drying oven at a temperature of 100°C for 2h to remove moisture, and the drying vacuum degree is 20KPa, then weigh 20g of the dried poly(1,4-butylene carbonate) diol into a 25mL three-necked flask, blow N2 into it, and add 1.8g of m-xylyl diisocyanate to the three-necked flask, and then add 50μL of dibutyltin dilaurate with a concentration of 1wt‰, and after the addition, raise the temperature to 80°C, and keep the reaction under N2 protection for 3h to obtain a modified polycarbonate diol;
[0063] S2: The modified polycarbonate diol, the hydroxymethyl-terminated polydimethylsiloxane with a molecular weight of 1000 and the hydroxyethyl-terminated polydimethylsiloxane with a molecular weight of 1000 were dried in a vacuum drying oven at a temperature of 105°C for 2h to remove moisture, and the drying vacuum degree was 30KPa, then 20g of the dried modified polycarbonate diol, 2.5g of the dried hydroxymethyl-terminated polydimethylsiloxane and 2.5g of the dried hydroxyethyl-terminated polydimethylsiloxane were weighed in a 25mL three-necked flask, N2 was introduced, 12.82g of m-xylyl diisocyanate was added, and then 50μL of dibutyltin dilaurate with a concentration of 1wt‰ was added. After the addition was completed, the temperature was raised to 80°C, and the reaction was kept warm for 2h under N2 protection;
[0064] S3: When the reaction liquid in step S2 is cooled to 45°C, 2.3 g of 1,4-butanediol and 7.1 g of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane are quickly added to the reaction liquid, and the mixture is quickly stirred evenly. The total time of addition and stirring is controlled to be 50 s. The product is then poured into a polytetrafluoroethylene tray, and then placed in an oven at 110°C for curing for 9 hours.
[0065] Example 7
[0066] An antioxidant polycarbonate polyurethane, the preparation method of which comprises the following steps:
[0067] S1: Dry poly(1,6-hexanediol carbonate) diol with a molecular weight of 700 in a vacuum drying oven at a temperature of 110° for 2.5 hours to remove moisture, and the drying vacuum degree is 20 KPa, then weigh 20 g of the dried poly(1,6-hexanediol carbonate) diol into a 25 mL three-necked flask, blow N2 into it, and add 1.28 g of m-xylyl diisocyanate and 1.78 g of 4,4'-dicyclohexylmethane diisocyanate to the three-necked flask, and then add 50 μL of dibutyltin dilaurate with a concentration of 1 wt‰, and after the addition, raise the temperature to 85°C, and keep the reaction for 3 hours under the protection of N2 to obtain a modified polycarbonate diol;
[0068] S2: The modified polycarbonate diol, the hydroxymethyl-terminated polydimethylsiloxane with a molecular weight of 1000 and the hydroxyethyl-terminated polydimethylsiloxane with a molecular weight of 1000 were dried in a vacuum drying oven at a temperature of 105°C for 2h to remove moisture, and the drying vacuum degree was 30KPa, then 20g of the dried modified polycarbonate diol, 2.5g of the dried hydroxymethyl-terminated polydimethylsiloxane and 2.5g of the dried hydroxyethyl-terminated polydimethylsiloxane were weighed in a 25mL three-necked flask, N2 was introduced, 7.1g of m-xylyl diisocyanate and 7.7g of isophorone diisocyanate were added, and then 50μL of dibutyltin dilaurate with a concentration of 1wt‰ was added. After the addition was completed, the temperature was raised to 80°C, and the reaction was kept warm for 2h under N2 protection;
[0069] S3: When the reaction liquid in step S2 is cooled to 45°C, 4.98 g of 1,4-butanediol is quickly added to the reaction liquid and quickly stirred evenly. The total time of adding and stirring is controlled to be 50 seconds. Then, the product is poured into a polytetrafluoroethylene tray and placed in a 120°C oven for curing for 8 hours.
[0070] Comparative Example 1
[0071] A polycarbonate-based polyurethane, the preparation method of which comprises the following steps:
[0072] S1: Dry poly(1,4-butylene carbonate) diol with a molecular weight of 1000 and polydimethylsiloxane terminated with ethylene glycol propyl ether with a molecular weight of 2000 in a vacuum drying oven at a temperature of 105°C for 2h to remove moisture. The drying vacuum degree is 30KPa. Then weigh 20g of the dried poly(1,4-butylene carbonate) diol and 5g of the dried polydimethylsiloxane terminated with ethylene glycol propyl ether into a 25mL three-necked flask, blow N2 into it, add 13.4g of 4,4'-dicyclohexylmethane diisocyanate, and then add 50μL of dibutyltin dilaurate with a concentration of 1wt‰. After the addition is complete, raise the temperature to 80°C and keep the reaction for 2h under N2 protection;
[0073] S2: When the reaction liquid in step S1 is cooled to 45°C, 3.60 g of 1,4-butanediol is quickly added to the reaction liquid and quickly stirred evenly. The total time of adding and stirring is controlled to be 30 seconds. Then, the product is poured into a polytetrafluoroethylene tray and placed in a 100°C oven for curing for 8 hours.
[0074] The performance of the anti-oxidative degradation polycarbonate polyurethane prepared in the embodiment of the present invention is similar, and the performance of related products is described through testing.
[0075] Experimental example
[0076] 1. Characterization Test
[0077] ①Infrared spectrum analysis
[0078] Fourier infrared spectrometer at 550-4000cm -1 The samples prepared in the examples and comparative examples were scanned within a range of 1600-1800 cm-1, and the spectra of the three carbonyl groups (1650-1800 cm-1) were fitted using the Gaussian-Lorentzian function of the Origin software. -1 ), wherein the infrared spectra of Example 1 and Comparative Example 1 are respectively as shown Figure 1 and Figure 2 As shown, at 1650cm -1 ~1800cm -1 The different peaks in the carbonyl stretching region indicate different bonding environments in the polymer matrix. -1 The peak at 1715 cm is the hydrogen bond (UUH bond) between the hard segments, indicating that there is a strong intermolecular force within the hard segments. -1 The peak at represents the hydrogen bond carbonyl stretching vibration (CUH bond) between the NH group of the hard segment and the C=O group of the soft segment, indicating the interaction between the hard and soft segments.
[0079] The spectra of all samples were decomposed using a Gaussian-Lorentzian function to accurately quantify the areas under these peaks, and the results are shown in Table 1.
[0080] Table 1
[0081]
[0082]
[0083] The data in the table show that the comparative sample has a peak at 1696 cm -1 The carbonyl group ratio at 1715 cm -1 The carbonyl ratio at is smaller, indicating that hydrogen bonds are more common in the hard segment, while the frequency between the hard segment and the soft segment is lower, which leads to obvious phase separation; while the modified polycarbonate diol (PCDL-HMDI-PCDL) in the example sample changes the hydrogen bond structure, the ratio of UU hydrogen bonds is reduced, and the ratio of CU hydrogen bonds is increased, which enhances the interaction between the soft segment and the hard segment, promotes phase mixing, and makes the soft segment less exposed to the outside, which is not easily affected by the external environment or chemical corrosion.
[0084] ② Differential scanning calorimetry
[0085] The test conditions are as follows: the samples of the embodiment and the comparative example are cooled to -50°C, and then heated to 100°C at a heating rate of 20°C / min, and the protective gas is nitrogen; Figure 3 Table 2 is the DSC heat flow curves of the samples of Example 1 and Comparative Example 1, and Table 3 is the statistical table of glass transition temperatures of the samples.
[0086] Table 2
[0087] sample <![CDATA[T g (℃)]]> sample <![CDATA[T g (℃)]]> sample <![CDATA[T g (℃)]]> sample <![CDATA[T g (℃)]]> Example 1 2.49 Example 3 2.81 Example 5 2.58 Example 7 2.61 Example 2 2.56 Example 4 2.96 Example 6 2.66 Comparative Example 1 -2.48
[0088] It can be seen from the table that the T g The soft segment mainly affects the elasticity and low temperature performance of the sample. The content of hydrogen bonds between the NH group of the hard segment and the C=O group of the soft segment in the example sample increases, the molecular force between the hard segment and the soft segment is enhanced, the solubility of the hard segment in the soft segment increases, and the rigidity of the hard segment chain is stronger, thereby increasing the rigidity of the soft segment, thereby improving the T of the sample. g .
[0089] ③X-ray photoelectron spectroscopy analysis
[0090] The elements on the surface of the samples of Example 1 and Comparative Example 1 were analyzed by X-ray photoelectron spectroscopy, with an acceleration voltage of 15 Kv and a beam current of 5 mA. Figure 4 This is the full XPS spectrum of the sample. Figure 5 The Si element fine spectrum shows that the increase in the silicon percentage in Example 1 is due to the introduction of the chain extender, which increases the entanglement density of the molecular chains in the polymer matrix, affects the phase separation behavior, and is beneficial for the hydroxyl-terminated polydimethylsiloxane fragments to migrate to the surface to form an anti-oxidative degradation protective layer.
[0091] 2. In vitro oxidative degradation test
[0092] The samples of the embodiment and the comparative example were immersed in 0.1M CoCl2 and 20wt% H2O2 solution and shaken at 37°C. In order to maintain the oxidation activity, the solution was changed every two weeks. The samples were collected at 0, 4, 8 and 12 weeks, respectively, and washed with 1% Triton X-100 detergent to remove the attached CoCl2. Subsequently, the samples were washed with deionized water and dried in a vacuum oven at 70°C for 48 hours before mechanical properties testing. The test results are shown in Table 3.
[0093] Table 3
[0094]
[0095] As can be seen from the table, the fracture stress of all samples has a significant decreasing trend after oxidation, indicating that the long-term oxidative environment leads to a decrease in mechanical strength, but compared with the comparative sample, the example sample is able to maintain a higher stress level, indicating that it can better maintain its mechanical properties despite the oxidative challenge. Figure 6The stress-strain curves of the original sample and the sample after oxidation for 12 weeks in Example 1 and Comparative Example 1 show that the fracture strain of the sample in Example 1 remains almost unchanged after 12 weeks of oxidation, which again shows that its mechanical properties are better and more resistant to oxidation. Then an electron microscope is used to scan and analyze the surface degradation of the sample. Figure 7 is the SEM image of the sample. It can be seen from the figure that the sample of Example 1 still maintains good mechanical properties and less pitting after 12 weeks of oxidation, which means that it has good resistance to oxidative degradation. Since the modified polycarbonate diol and chain extender are introduced into the sample of Example 1, they increase the entanglement density of the molecular chains in the polyurethane matrix. In addition, the modified polycarbonate diol structure enhances the overall intermolecular force in the polymer matrix. Therefore, the free radicals generated by the decomposition of hydrogen peroxide catalyzed by cobalt ions in the oxidant cobalt chloride are more difficult to penetrate the material and cause chain breakage, thereby improving the oxidative stability of the sample.
[0096] 3. Biocompatibility Test
[0097] The samples of the embodiment were characterized as follows: ① Hemolysis: 1 mL of 5% red blood cell suspension was added to the sample; in addition, the red blood cell suspension was diluted to 5% with PBS buffer and deionized water as a negative control and a positive control, respectively; incubated at 37°C for 2 h, the supernatant was extracted after centrifugation, the absorbance of hemoglobin was determined by enzyme labeling, and compared with the positive control and the negative control, and the hemolysis rate was calculated. The results are shown in Table 4.
[0098] Table 4
[0099]
[0100] It can be seen from the table that the hemolysis rate of each sample is lower than the industry standard (2%), indicating that the antioxidant degradation polycarbonate polyurethane prepared by the present invention has good blood compatibility.
[0101] ② Cytotoxicity: Mouse fibroblasts (L929 cells) were co-cultured with the sample extract for 1 day and 3 days, and the viability of the L929 cells was evaluated using the CCK-8 method. The evaluation results are shown in Table 5. It can be seen from the table that the viability of the L929 cells in the sample extract of the embodiment is good, further illustrating that the antioxidant degradable polycarbonate polyurethane prepared by the present invention has good compatibility with cells.
[0102] Table 5
[0103]
[0104] ③ Inflammation in vivo: The samples of Example 1 and Comparative Example 1 were cut into 1 cm × 1 cm pieces and implanted subcutaneously in rats, respectively. The implanted samples were taken out after 7 days and 14 days, the tissues around the samples were removed, and the samples were fixed with 4 wt% paraformaldehyde fixative. After dehydration, the samples were embedded in paraffin, and then the samples were stained with hematoxylin-eosin (HE) and observed under a microscope. The stained images are shown in FIG. Figure 8 As shown in the figure, it can be seen that the sample in Example 1 has fewer inflammatory cells around it, a thin fibrous capsule, and good biocompatibility.
[0105] The present invention prepares a novel antioxidant degradable polycarbonate polyurethane by modifying raw materials such as polycarbonate diol, diisocyanate and chain extender. The sample of the embodiment shows better phase mixing, mechanical properties and oxidation stability, and has low cytotoxicity and biotoxicity, which makes the antioxidant degradable polycarbonate polyurethane of the present invention a very promising long-term implant biomaterial, solving the limitation of poor long-term stability of existing polyurethane materials.
[0106] Although the specific implementation of the present invention is described in detail in conjunction with the embodiments, it should not be understood as limiting the scope of protection of this patent. Within the scope described in the claims, various modifications and variations that can be made by those skilled in the art without creative work still fall within the scope of protection of this patent.
Claims
1. A method for preparing an oxidatively degradable polycarbonate polyurethane, characterized in that: The following steps are involved: S1: mixing the vacuum-dried polycarbonate diol, diisocyanate and a catalytic amount of a catalyst, and reacting them under the protection of an inert gas for 2 to 3 hours to obtain a modified polycarbonate diol; the reaction temperature is 80 to 85° C., and the catalyst is an organic metal catalyst; S2: vacuum drying the modified polycarbonate diol and the hydroxyl-terminated polydimethylsiloxane, mixing the dried modified polycarbonate diol, the dried hydroxyl-terminated polydimethylsiloxane, the diisocyanate and a catalytic amount of the catalyst, and reacting them for 1.5 to 2 hours under the protection of an inert gas at a reaction temperature of 70 to 80° C.; S3: After the reaction liquid in step S2 is cooled to 45-50° C., a chain extender is added to the reaction liquid, and the mixture is stirred evenly and solidified to obtain the product.
2. The method for preparing the anti-oxidative degradation polycarbonate polyurethane according to claim 1, characterized in that: The diisocyanate is at least one of isophorone diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 4,4'-dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, toluene diisocyanate and meta-xylyl diisocyanate; the organic metal catalyst is dibutyltin dilaurate or bismuth laurate; and the inert gas is N2.
3. The method for preparing the anti-oxidative degradation polycarbonate polyurethane according to claim 1, characterized in that: In step S1, the drying vacuum degree is 20-40 KPa, the drying temperature is 100-110° C., and the drying time is 2-2.5 h.
4. The method for preparing the anti-oxidative degradation polycarbonate polyurethane according to claim 1 or 2, characterized in that: The polycarbonate diol in step S1 is (1,4-butanediol carbonate) diol with a molecular weight of 500-2000 and / or poly (1,6-hexanediol carbonate) diol with a molecular weight of 500-2000; the molar ratio of the polycarbonate diol to the diisocyanate is 2-2.2:
1.
5. The method for preparing the anti-oxidative degradation polycarbonate polyurethane according to claim 1, characterized in that: In step S2, the drying vacuum degree is 20-40 KPa, the drying temperature is 90-110° C., and the drying time is 1.5-2 h.
6. The method for preparing the anti-oxidative degradation polycarbonate polyurethane according to claim 1 or 2, characterized in that: The hydroxyl-terminated polydimethylsiloxane in step S2 is at least one of hydroxymethyl-terminated polydimethylsiloxane with a molecular weight of 500 to 2000, hydroxyethyl-terminated polydimethylsiloxane with a molecular weight of 500 to 2000, hydroxybutyl-terminated polydimethylsiloxane with a molecular weight of 500 to 2000, and ethylene glycol propyl ether-terminated polydimethylsiloxane with a molecular weight of 500 to 2000; the mass ratio of the modified polycarbonate diol to the hydroxyl-terminated polydimethylsiloxane is 4:1; the ratio of the isocyanate index NCO / OH in the reaction system of step S2 is 1.01 to 1.
05.
7. The method for preparing the anti-oxidative degradation polycarbonate polyurethane according to claim 1 or 2, characterized in that: The chain extender in step S3 is one or two of 1,3-bis(4-hydroxybutyl)tetramethyldisiloxane, 1,4-butanediol and 1,6-hexanediamine. When the chain extender includes two components, the molar ratio of the two chain extenders is 1:1; the total content of diisocyanate and chain extender in the obtained antioxidant degradation polycarbonate polyurethane is 43-47wt%.
8. The method for preparing the anti-oxidative degradation polycarbonate polyurethane according to claim 1, characterized in that: The total time for adding the chain extender and stirring in step S3 is 30 to 60 seconds; the curing temperature is 100 to 120° C., and the curing time is 8 to 10 hours.
9. An oxidatively degradable polycarbonate polyurethane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. An application of anti-oxidative degradation polycarbonate polyurethane, characterized in that: The polycarbonate-based polyurethane described in claim 9 is used to prepare medical implant materials.
Citation Information
Patent Citations
Polysiloxane polyurethane supramolecular elastomer as well as preparation method and application thereof
CN116178666A
Biocompatible and biostable polydimethylsiloxane type polyurethane urea for chain extension of ureido chain extender as well as preparation and application of biocompatible and biostable polydimethylsiloxane type polyurethane urea
CN118108921A
Polyurethanes for medical implantation
US20070244290A1
Hydrolytically-and proteolytically-stable polycarbonate polyurethane silicone copolymers
US5863627A
